(untitled) (Journal of the College of Basic Education, 2023)
This search involved synthesis of several new N-Substituted -3-chloro- 2-azetidinones which were known as a high medicinal effectiveness for 2, 4-Diamino-6-hydroxy pyrimidin in two steps. The first step included preparation Shiff bases (1-6) by condensation of 2, 4-Diamino-6-hydroxy pyrimidin with many substituted aldehydes(4-hydroxy benzaldehyde, 2- bromobenzaldehyde, 4-dimethyl amino benzaldehyde, = 4-nitro benzaldehyde, salicylaldehyde, 4-chlorobenzaldehyde), then the second step included, preparation new six azetidinones compounds (7-12) by reaction of chloroacetylchloride with the prepared Schiff bases in the first step in the presence of triethylamine. The structures of synthesized compounds were- characterized by physical properties (FT-IR, UV and some of them by ’H-NMR, C_NMR spectroscopy) were recorded.